2020
DOI: 10.2166/wp.2020.061
|View full text |Cite
|
Sign up to set email alerts
|

Regional difference of water use in a significantly unbalanced developing region

Abstract: With a service for the most developed economy and dense population in China, the water use of Guangdong province shows distinct regional difference and is subject to multiple driving forces. The regional differences of total water use (TWU) and water use efficiency (WUE) for Guangdong province and its four sub-regions (i.e. Pearl River Dealt region (PRD), Eastern Wing (YD), Western Wing (YX), and Northern Mountain Region (YB)) were quantified by Theil index, and the influence of various variables on WUE was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The most populous and economically important province in China is also the first in sewage discharge. Over the past 32 years, it has experienced rapid and significant regional socioeconomic development imbalances (He et al, 2020). With a critical shortage of available freshwater resources per capita (less than a quarter of the world average), severe water quality pollution, uneven spatial and temporal distribution (densely distributed in the mid-Guangdong region), significant inter-annual variability in water resources (Xian et al, 2022), and the water supply security of the lower reaches of the Pearl River Delta is threatened by upstream runoff decrease and downstream saltwater intrusion (He et al, 2018), the province is now faced with a huge pressure on water supply security, both to ensure high-quality economic and social development and to protect the water environment.…”
Section: Main Contents Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The most populous and economically important province in China is also the first in sewage discharge. Over the past 32 years, it has experienced rapid and significant regional socioeconomic development imbalances (He et al, 2020). With a critical shortage of available freshwater resources per capita (less than a quarter of the world average), severe water quality pollution, uneven spatial and temporal distribution (densely distributed in the mid-Guangdong region), significant inter-annual variability in water resources (Xian et al, 2022), and the water supply security of the lower reaches of the Pearl River Delta is threatened by upstream runoff decrease and downstream saltwater intrusion (He et al, 2018), the province is now faced with a huge pressure on water supply security, both to ensure high-quality economic and social development and to protect the water environment.…”
Section: Main Contents Methodologymentioning
confidence: 99%
“…Over a period of 26 years, combined per capita water consumption has gradually declined, with the province's total water use decreasing by 8.6%. Despite ranking first in GDP among all provinces in China since 1988 due to its early implementation of reforms and opening up policies, regional disparity persists within Guangdong province (He et al, 2020; Zhang et al, 2018), leading to variations in resource use efficiency. Consequently, there are areas in Guangdong province where the demand for water exceeds the available supply, resulting in conflicts.…”
Section: Methodology and Datamentioning
confidence: 99%
“…For example, Dean et al (2009) found no significant effect of the level of environmental regulations on FDI inflows in China's provinces, while Zhang and Fu (2012) reached the opposite result. However, uneven development also exists among different cities in a province (He et al, 2020), so province-level studies still overlook the impact of regional differences within host countries on the location choices of acquirers.…”
Section: Introductionmentioning
confidence: 99%